2012
DOI: 10.1210/me.2011-1229
|View full text |Cite
|
Sign up to set email alerts
|

Autotaxin and Its Product Lysophosphatidic Acid Suppress Brown Adipose Differentiation and Promote Diet-Induced Obesity in Mice

Abstract: Brown adipose tissue is a thermogenic organ that dissipates stored energy as heat to maintain body temperature. This process may also provide protection from development of diet-induced obesity. We report that the bioactive lipid mediator lysophosphatidic acid (LPA) markedly decreases differentiation of cultured primary brown adipocyte precursors, whereas potent selective inhibitors of the LPA-generating enzyme autotaxin (ATX) promote differentiation. Transgenic mice overexpressing ATX exhibit reduced expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 47 publications
1
82
0
Order By: Relevance
“…On the other hand, it has also been reported that ENPP2 expression is elevated in adipose tissue from diabetic db/db mice and that DIO mice show no significant changes in ENPP2 expression (17). What's more, earlier studies produced contradictory results regarding BAT mass, locomotor activity, thermogenic profiles, and systemic metabolism (6,7). The precise mechanisms responsible for these discrepancies between the results of the current study and those earlier ones are not immediately clear, but there were several experimental differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has also been reported that ENPP2 expression is elevated in adipose tissue from diabetic db/db mice and that DIO mice show no significant changes in ENPP2 expression (17). What's more, earlier studies produced contradictory results regarding BAT mass, locomotor activity, thermogenic profiles, and systemic metabolism (6,7). The precise mechanisms responsible for these discrepancies between the results of the current study and those earlier ones are not immediately clear, but there were several experimental differences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dusaulcy et al (6) reported that adipocytespecific Enpp2 knockout (KO) mice fed a high-fat diet showed greater adiposity and less systemic insulin resistance than control mice, with no difference in food intake. By contrast, Federico et al (7) reported that fat pad weights were higher in mice overexpressing Enpp2, although locomotor activities, thermogenic profiles, and systemic metabolism were unchanged. These apparently contradictory results prompted us to examine the role of Enpp2 in systemic metabolism.…”
mentioning
confidence: 89%
“…OEA is one of the endocannabinoid-like metabolites, which is modulating satiety and decreases body weight through activation of peroxisome proliferatoractivated receptor-a but do not regulate the endocannabionid system (Capasso and Izzo, 2008). Lysophosphatidic acid is another bioactive lipid that mediates adipocyte proliferation and differentiation through downregulation of peroxisome proliferator-activated receptor-g and is involved in obesity (Nobusue et al, 2010;Federico et al, 2012). Enterolactone and enterodiol are bacterial metabolites, produced by certain bacteria and have been reported to exert beneficial effects in the body (Woting et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of two decades of research, a large number of studies have established that in addition to cellautonomous cancer hallmarks such as differentiation ( 58,(103)(104)(105)(106), survival (107)(108)(109)(110)(111)(112), proliferation ( 58,(113)(114)(115)(116), and migration/metastatic behavior ( 50, 74,92,[117][118][119][120][121][122], the aberrant expression/amplifi cation of ATX activity can also dysregulate multiple cancer pathobiology systemic hallmarks including angiogenesis ( 119,123 ), metabolic homeostasis ( 56-59, 104, 124, 125 ), and immune system function ( 126 ).…”
Section: Role In Physiology and Cancer Pathophysiologymentioning
confidence: 99%